Biogeochemical Processes of Biogenic Elements in China Marginal Seas - Song, Jinming (Advanced Topics in Science and Technology in China,, 2010)
"Biogeochemical Processes of Biogenic Elements in China Marginal Seas" is the first monograph dedicated to this topic. The book mainly presents the latest research achievements of China's national research projects about the biogenic element cycling processes in China marginal seas starting in 1999. By describing the biogeochemical processes of China marginal seas, including the Bohai Sea, the Yellow Sea, the East China Sea, and the South China Sea, it covers almost all kinds of typical ecosystems' regional responses to global oceanic changes of the estuarine ecosystem, the continental shelf ecosystem, the upwelling ecosystem, the coral reef ecosystem, and the mangrove ecosystem. It will be of great interest to scientists and researchers in marine science. Dr. Jinming Song is a professor at Institute of Oceanology, Chinese Academy of Sciences.